Mortality Rate in Mechanically Ventilated Neonates: A Developing Country Experience - Wesam A. Mokhtar; Laila Sherief; Naglaa M. Kamal; Sherief Kamel (Mashhad University of Medical Sciences, 2021)
Background: Although a great improvement has been achieved in the outcome of sick neonates with the effectivewidespread introduction of mechanical ventilation in neonatal intensive care units, a significant proportion of highfatality is still detected among such patients. This study was conducted to identify the complications, outcome, andcauses of death among a sample of critically ill Egyptian neonates subjected to mechanical ventilation using pressurecontrolledmode.  Methods: The statistical population of this study were prospectively enrolled in the current study and consisted of 240 eligible patients fulfilling the study inclusion criteria. Those with multiple congenital malformations or post-surgical cases were excluded from the study. The data regarding medical record, clinical examination, indication for mechanicalventilation, complications related to mechanical ventilation, and outcome were collected, recorded, and analyzed. Results: The incidence of complications related to mechanical ventilation was obtained at 104 (43.3%), and VAP observedan increase (20%). Furthermore, the complications related to disease patterns were reported to be 56.7% and 22.5% forsepsis and septic shock. It has been revealed that 124 (51.7%) of the studied neonates had favorable outcomes; however,the remaining 116 (48.3%) of the subjects passed away with a significant increase in the incidence of VAP (P=0.013). Itwas reported that smaller gestational age and lower birth weight were the most significant risk factors. Conclusion: In Egypt; as a developing country, the mortality rate among critically ill neonates undergoing mechanicalventilation with pressure-controlled mode was significantly high, approaching 48.3%, with VAP being the mostcommon cause of death.